In Search of Germany. - Mertes, Michael 1953- (Taylor and Francis, 2018)
Intro -- Half Title Page -- Title Page -- Copyright Page -- Contents -- Preface -- Germany's Social and Political Culture: Change Through Consensus? -- Democracy in Germany -- Rebuilding of a Nation: The Germans Before and After Unification -- Germanyâ's Choice -- Germany at the Crossroads: On the Efficiency of the German Economy -- Immigration and Social Peace in United Germany -- On German Identity -- Political Dynamics in Germany -- Crisis of Unification: How Germany Changes -- Multi-German Germany -- Aspects of Society and Identity in the New Germany -- Two Catastrophes, Two Causes, and How the Germans Dealt with Them -- The Role of the Protestant Church in German Unification -- Observations on the Political Class in Germany -- The German Way of Dealing with a Stasi Past -- Coda -- Index